Power Split Control Strategy for an EV Powertrain With Two Propulsion Machines - Yavasoglu, Huseyin Ayhan; Shen, Junyi; Shi, Chuan; Gokasan, Metin; Khaligh, Alireza (Institute of Electrical and Electronics Engineers (IEEE), 2015)
In this paper, a power split control strategy is proposed for an electric vehicle (EV) powertrain with two propulsion machines and a battery/ultra-capacitor (UC) hybrid energy storage system (HESS). The proposed power split control strategy consists of two stages. In the first stage, the load power is split between the two propulsion machines to obtain the highest powertrain efficiency in both propulsion and regenerative braking modes. A real-time implementable power split control strategy is proposed to benefit from complementary operation features of these two propulsion machines. In the second stage, the load power is split between the battery pack and UC in the HESS. To optimize the power split in HESS, a convex optimization problem is formulated to minimize the battery power magnitude and battery current variations to extend the battery lifetime. The implementation of proposed power split control strategy in the powertrain of an EV with two propulsion machines will potentially result in up to 10% improvement in the powertrain efficiency and up to 82% extension of the battery lifetime. The improvement of propulsion efficiency will in turn lead to up to 27% extension of all-electric driving range.